Viksit Bharat Sankalp Yatra: The Health Perspective - Bano, Tanveer; Varghese, Anila (Indian Journal of Community Health, 2023)
In 2023, India became the most populated country in the world with a population of 1.42 billion, providing it potential for significant economic growth by leveraging the demographic dividend.(1,2) As India becomes the global super power that the nation has potential to be, it is imperative to prioritize the well-being of the citizens. The government, being the elected representative body of people, holds the responsibility for ensuring the welfare of the masses. The Government of India periodically introduces welfare programs to cater to a diverse spectrum of the population.(3) As per the 2022 Union Budget, there are 740 central sector schemes.(4) The effectiveness of any program lies in its ability to reach its eligible beneficiaries. Unfortunately, several welfare schemes provided by the government do not reach its eligible recipients due to lack of awareness.(5) An information drought occurs, especially in rural areas despite the government’s best efforts in creating awareness through radio, TV, print or online media.(6)